Analisis Perbandingan Pengungkapan Tata Kelola Perusahaan Pada Bank Umum Konvensional Dan Bank Umum Syariah Di Indonesia 2010-2013 - Putri, Gita Danastri; Sholihin, Mahfud (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2015)
This study aims to analyze the disclosure level ofcorporate governance report in the annual report of Conventional Commercial Bank (BUK) and Islamic Commercial Bank (BUS) in Indonesia in 2010-2013 with the indicators mentioned in the Bank Indonesia Regulation Number 8/4 / PBI / 2006 which was later revised by Bank Indonesia Regulation No. 8/14 / PBI / 2006 for the BUK and Bank Indonesia Regulation No. 11/33 / PBI / 2009 for BUS. In addition, this study analyzes and compares the growth rate of the disclosure. To achieve the objectives of the research, this study uses content analysis method. The results show that of the eight BUSs studied, only three banks (38%) provide corporate governance disclosure with more than 75%. While for the BUKs sampled, all provide corporate governance disclosure with more than 75%. Related to the growth of the disclosure, the average growth of disclosure for four years,for BUS is 6.27% and for BUK is 3.41%. The highest difference between the disclosure level of BUS and BUK is about 50%.Keywords: content analysis; Conventional Commercial Bank (BUK); Islamic Commercial Bank (BUS); disclosure; corporate governance;